A VR Experimental Study on the Influence of Chinese Hotel Interior Color Design on Customers’ Emotional Experience - Jian Xu; Muchun Li; Kaizhong Cao; Fangqi Zhou; Boyi Lv; Ziqi Lu; Zihan Cui; Kailiang Zhang (Buildings, 2022)
As an important part of a hotel’s internal environment, color design affects not only customers’ hotel stay experiences, but also their check-in experiences. However, how hotel guests’ emotional experiences are affected by interior color design is understudied in China. Drawing on the theory of color psychology, we designed a Virtual Reality (VR) experiment and a questionnaire to explore how hotel guests’ emotional experience can be influenced by the color scheme of hotel interior color design. The results show that hotel rooms decorated in yellow have a pleasurable effect, those decorated in gray a calming effect, and those decorated in blue a relatively neutral effect. Young participants have more negative emotional responses to rooms decorated in dark yellow. The emotional impact of both gray and yellow with higher grayscale values shifts from positive to negative with the improvement of customers’ educational background. Low grayscale color schemes are preferred over high grayscale ones, and indoor environments with synergistic colors are preferred over contrasting colors. It is also found that male subjects tend to have more positive emotional reactions to all color schemes than females. For most subjects, age and education have no effect on their emotional reactions to different color schemes. These findings have important implications for hotel interior environment color design.